(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Energy efficiency is important in saving energy needs and reducing budget funds for hospital operations. There needs to be an effort to save energy using renewable solar energy sources. This study aimed to determine the optimal energy gain, the Break Event Point value, and the PV efficiency on the facade and roof of the RSUP Trauma Center NTB. It was conducted using a simulation method with the Rhino Grasshopper application and Open Studio Sketchup. It also involved collecting data and creating 3D input models into the Grasshopper and Open Studio plugin. The next stage was simulating OTTV, Cooling Load, and Photovoltaic in the test room within a year. The optimal PV shading based on the simulation was applied to the facade of the Trauma Center building. The results showed that laying PV on the roof would be more effective within 20 years than on the façade. This is because the efficiency value on the roof is higher than on the facade. The PV system measuring at a distance of 0.8 m on the facade and roof is 4.21% and 8.82% efficient, respectively. The efficiency at a distance of 1 m on the façade and roof is 6.31% and 7.81%, respectively.